A healthy eating score is inversely associated with depression in older adults: results from the Chilean National Health Survey 2016–2017. Issue 10 (13th October 2022) - Lanuza, Fabian; Petermann-Rocha, Fanny; Celis-Morales, Carlos; Concha-Cisternas, Yeny; Nazar, Gabriela; Troncoso-Pantoja, Claudia; Lassere-Laso, Nicole; Martínez-Sanguinetti, María Adela; Parra-Soto, Solange; Zamora-Ros, Raul; Andrés-Lacueva, Cristina; Meroño, Tomás
Abstract: Objective: To investigate the relationship of a healthy eating score with depression in Chilean older adults. Design: Cross-sectional study. Setting: Older adults from the Chilean National Health Survey 2016–2017. Associations were analysed using complex samples multivariable logistic regressions adjusted for age, sex, socio-demographic, lifestyles (physical activity, smoking, alcohol consumption and sleep duration), BMI and clinical conditions (hypertension, diabetes, hypercholesterolaemia and cardiovascular diseases). Participants: The number of participants was 2031 (≥ 60 years). The Composite International Diagnostic Interview-Short Form was applied to establish the diagnosis of major depressive episode. Six healthy eating habits were considered to produce the healthy eating score (range: 0–12): consumption of seafood, whole grain, dairy, fruits, vegetables and legumes. Participants were categorised according to their final scores as healthy (≥ 9), average (5–8) and unhealthy (≤ 4). Results: Participants with a healthy score had a higher educational level, physical activity and regular sleep hours than participants with an average and unhealthiest healthy eating score. Participants classified in the healthiest healthy eating score had an inverse association with depression (OR: 0·28, (95 % CI 0·10, 0·74)). Food items that contributed the most to this association were legumes (15·2 %) and seafood (12·7 %). Conclusion: Older adults classified in the healthiest healthy eating score, characterised by a high consumption of legumes and seafood, showed a lower risk for depression in a representative sample of Chilean population.